Segregation of D1 and D2 dopamine receptors in the striatal direct and indirect pathways: An historical perspective - Gerfen, Charles R. (Frontiers in Synaptic Neuroscience, 2023)
The direct and indirect striatal pathways form a cornerstone of the circuits of the basal ganglia. Dopamine has opponent affects on the function of these pathways due to the segregation of the D1- and D2-dopamine receptors in the spiny projection neurons giving rise to the direct and indirect pathways, An historical perspective is provided on the discovery of dopamine receptor segregation leading to models of how the direct and indirect affect motor behavior.